Contemplating UDHR and Indian Constitutional guarantees: An analysis (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The Universal Declaration is a foundational text that establishes the United Nations. The UDHR is recognized by the Guinness Book of Records as the Most Translated Documentglobally. Despite lacking legal enforceability, the Declaration has been either adopted or had an impact on numerous national constitutions since 1948. Furthermore, it has provided the basis for an increasing number of domestic and international legislations, as well as agreements, and regional, national, and sub-national organizations that safeguard and advance human rights. The importance of a nation's interest and the security of the state must be considered while interpreting the Universal Declaration, as well as every article that addresses fundamental rights, including Article 21 of the Indian Constitution. Several political rights, which are protected by the Universal Declaration of Human Rights (UDHR), are also recognized as fundamental rights in Part III of the Constitution. This research aims to investigate the relationship between the complex national circumstances of India and the universal human rights ideals established in the UDHR. Researchers intend to evaluate the implementation and relevance of the UDHR within the context of India by conducting an analysis of the socio-political landscape, cultural diversity, and legal framework of India respectively. The purpose of this article is to provide light on the difficulties and opportunities that are associated with the upholding of universal human rights principles in India.